2021
DOI: 10.1016/j.molcel.2021.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chromatin context on Cas9-induced DNA double-strand break repair pathway balance

Abstract: Summary DNA double-strand break (DSB) repair is mediated by multiple pathways. It is thought that the local chromatin context affects the pathway choice, but the underlying principles are poorly understood. Using a multiplexed reporter assay in combination with Cas9 cutting, we systematically measure the relative activities of three DSB repair pathways as a function of chromatin context in >1,000 genomic locations. This reveals that non-homologous end-joining (NHEJ) is broadly biased toward euchroma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 98 publications
4
145
1
Order By: Relevance
“…In contrast, a recent study that used a sequencing-based reporter screen to investigate the impact of chromatin context on CRISPR-Cas9-induced DSBs did reveal differences in repair pathway usage in H3K27me3 regions [ 127 ]. This reporter was randomly integrated in >1000 different locations in the genome of human cancer cells and can be cleaved by Cas9.…”
Section: Facultative Heterochromatinmentioning
confidence: 99%
“…In contrast, a recent study that used a sequencing-based reporter screen to investigate the impact of chromatin context on CRISPR-Cas9-induced DSBs did reveal differences in repair pathway usage in H3K27me3 regions [ 127 ]. This reporter was randomly integrated in >1000 different locations in the genome of human cancer cells and can be cleaved by Cas9.…”
Section: Facultative Heterochromatinmentioning
confidence: 99%
“…NHEJ, on the other hand, is preferred in heterochromatic regions and at sites where H4 is demethylated at lysine 20 (H4K20me2; Karakaidos et al, 2020). Recently, the pathway balance between NHEJ and MMEJ as influenced by chromatin configuration has also been mapped (Schep et al, 2021). This study showed that MMEJ is more active than NHEJ in specific heterochromatin contexts, namely late replicating regions, lamina associated regions, and at H3K9me2 sites.…”
Section: Tissue Specific Effects Of Differentiation and Chromatin Statusmentioning
confidence: 88%
“…This study showed that MMEJ is more active than NHEJ in specific heterochromatin contexts, namely late replicating regions, lamina associated regions, and at H3K9me2 sites. Moreover, MMEJ was shown to compete with SSTR (Schep et al, 2021). Therefore, systematically mapping chromatin environments across cell types can inform avenues for regulation to successfully install CRISPR edits which rely on the incorporation of repair templates.…”
Section: Tissue Specific Effects Of Differentiation and Chromatin Statusmentioning
confidence: 99%
“…In addition to H3K9me3, H3K27me3 also decorates heterochromatin regions, such as those associated with the lamina, and DSBs in these H3K27me3-enriched regions show increased repair by MMEJ ( Lemaître et al, 2014 ; Schep et al, 2021 ). Interestingly, chemical inhibition of H3K27 and not of H3K9 methyltransferases shifted the MMEJ/NHEJ balance toward NHEJ ( Schep et al, 2021 ), arguing that the H3K27me3 heterochromatin mark either stimulates MMEJ or inhibits NHEJ. However, the underlying molecular mechanisms still need to be elucidated and the impact of H3K27me3 on HR is unknown.…”
Section: Heterochromatin Features Direct Dsb Repair Pathway Choicementioning
confidence: 99%